Memorix histologie - Balko, Jan; Tonar, Zbyněk; Varga, Ivan; Hudák, Radovan; Zavázalová, Šárka (Stanislav Juhaňák - TRITON, 2021)
Vysokoškolská učebnice, která se zaměřuje na histologii.
Keywords: Histology; histologie